Body image: differences and similarities between Colombian and Dutch teenagers - Ana María Ochoa Hoyos (Universidad de Antioquía, 2007)
Objective: to explore the relationship between eating patterns and body image perception in two different cultural adolescent groups, one from Colombia and the other one from The Netherlands. Methods: this is a qualitative study, recruited participants were teenaged women, eight from Medellin nine from Amsterdam; the data was collected in both groups, a survey was applied first to focal groups and then to individuals willing to talk about their eating patterns and other practices related to their body image perception. Results: Netherlands and Colombia could be considered Western countries but there are some differences in the way that adolescent girls perceive the body image and how they have to deal with the social pressure on them to get the ideal body. The ideal body image promoted by popular media in both countries is almost the same; but in Colombia, adolescents use their bodies in a manner to get power and control, and their families and peers put more pressure on them than in the Netherlands. Conclusions: teenagers perceive the ideal body as a symbol to have power and control and to acquire identity. Studying the same issue in two different cultures, allows social health programs to get the real idea about adolescent behaviors in order to make changes according to the cultural settings.